Optimizing Digital Marketing in Building the Image and Public Trust of Islamic Boarding Schools in the Era of Educational Technology - Ittaqillah Haitsuma Kunta; Rifka Jannatul Firdausiyah; Moh. Kamil; Muhammad Durrin Ni'am; Siti Nur Aviatun Hasanah; Moh. Rofik; Badrul Mudarris (Educazione: Journal of Education and Learning, 2024)
The development of educational technology encourages Islamic educational institutions, including Islamic boarding schools, to innovate in building their image and increasing public trust. One effort is through the implementation of digital marketing strategies that utilize various social media platforms and official websites. This study aims to analyze how digital marketing is optimized in building the image of institutions and increasing public trust in Islamic boarding schools in the era of educational technology. This study uses a qualitative approach with a case study type. Data collection techniques are carried out through interviews, observations, and documentation of digital marketing activities carried out by Islamic boarding schools. The data obtained are then analyzed descriptively to understand the patterns and strategies applied. The results of this study indicate that digital marketing carried out consistently and planned can increase visibility and shape a positive image of Islamic boarding schools in the community. The use of informative, educational, and religious content is a major factor in building public trust. In addition, transparency of information through digital media also contributes to increasing the credibility of institutions. Practically, this study provides an overview of the importance of optimizing digital marketing in building image and public trust. Theoretically, this research enriches the study of Islamic education marketing in the digital era, particularly in the aspect of the relationship between institutional image and public trust.